ADAPTATION TIMING TO DENTURES IN RELATION TO DEFECT TOPOGRAPHY, AGE, AND PSYCHO-EMOTIONAL STATE OF PATIENTS - Azimova Shakhnoza Shukhratovna (Bright Mind Publishing, 2025)
In recent years, there have been significant advances in providing quality care to patients in the world dental practice. This was facilitated by certain achievements in the study of the etiology of dental diseases, the creation of effective methods of their treatment using the latest achievements in dental materials science and modern medical equipment. At the same time, as evidenced by clinical experience, doctors increasingly have to deal with patients who complain of a poorly made prosthesis, which is, nevertheless, a foreign body, due to pain and tactile discomfort for the first time after their establishment in the mouth.
Keywords: Dental prosthesis, fixation, quality of life, psychoprophylactics.